Determination of dimethyl-and diethylmercury with HPLC-CVAAS by on-line UV-irradiation - Falter, Ralf; Schöler, Heinz Friedrich (Fresenius' journal of analytical chemistry, 1994)
A technique has been developed for the determination of dimethyl- and diethylmercury. It is based on the separation by reversed-phase HPLC, on-line decomposition of the dialkylmercury compounds by H2O2 and UV-irradiation, reduction with alkaline sodium borohydride, followed by gas liquid separation of mercury vapour and determination by cold vapour atomic absorption detection. The method permits the simultaneous determination of dimethyl- and diethylmercury by RP C18 HPLC-CVAAS. The limit of detection (S/N=3) for both compounds was calculated to be about 30 ppb.
Gesehen am 08.02.2023